KEANEKARAGAMAN JENIS KANTONG SEMAR ( Nepenthes spp. ) DI CAGAR ALAM DOLOK SIBUAL-BUALI - Muhaimin Zikri Pratama; Pindi Patana; Yunasfi Yunasfi (Program studi Kehutanan USU, 2016)
Nepenthes is a carnivorous plant that has a unique bag, each end of the leaf. This unique bag can trap insects or other small animals, as in the pocket there is nectar glands (glands honey) that can trap insects especially with the sweet taste. This research was conducted in the Nature Reserve Dolok Sibual Buali from August until October 2014. This study aims to determine the diversity of plant species in the area of ​​Nepenthes Nature Reserve Dolok Sibual-Buali, North Sumatra and Knowing dominance Nepenthes plants are found in the Nature Reserve Dolok Sibual -Buali, North Sumatra. This survey using the cluster method to determine the area of ​​the sample is based on consideration of the existence of Nepenthes (searching the sample). From the research results can be seen, there are 5 types of Nepenthes in Cagar Alam Dolok Sibual Buali, namely N. Bongso N. ovata, N. reinwardtiana, rhombicaulis N., and N. tobaica. Total clumps most is N. reinwardtiana with 169 clumps and clumps least number is N. ovata with 54 clumps. Keywords: Cagar Alam Dolok Sibual Buali, species diversity, Nepenthes.